Changes in New Zealand forest plant communities following the prehistoric extinction of avian megaherbivores. (2nd November 2016) - Wood, Jamie R.; Wilmshurst, Janet M.
Abstract: Questions: Following the mid 15th century AD extinction of moa (Aves: Dinornithiformes) there was a 400‐yr period when large herbivores were absent from New Zealand's terrestrial ecosystems. This ended with the introduction of mammalian herbivores by European settlers in the 19th century. For at least 40 yr researchers have speculated about how New Zealand's vegetation communities might have responded to the 'herbivore gap'. Did plant taxa once consumed by moa flourish in forest understoreys without large herbivores to browse them? Did forest understoreys become denser, preventing regeneration of long‐lived conifers and altering forest composition? Such questions remain to be tested using palaeoecological records. Location: Three locations on South Island, New Zealand (from <20 to 750 m a.s.l) where forest has not been burned since human settlement, and where there has been no obvious geological or climatic disturbance events over the past 1000 yr that have influenced vegetation dynamics. Methods: We identified and quantified pollen grains and fern spores from soil/peat cores taken beneath, or adjacent to, tall forest canopies. Soil/peat samples from the cores were radiocarbon dated and Bayesian age–depth models were constructed for each core, from which depths corresponding to the herbivore gap period were identified. Changes in pollen/spore abundances occurring within the herbivore gap were identified and critically examined for consistency between cores and likelihood of being caused by loss of browsing pressure from large herbivores (through comparison with plant taxa known to have been consumed by moa). Results: Ground fern spores and Coprosma pollen exhibited increases in relative abundance at all three sites during the herbivore gap. Both occur frequently in moa coprolites and gizzard content, and so can be interpreted as possible responses to moa extinction. However, other changes in pollen assemblages at this time were inconsistent between sites, or could be better explained as being related to anthropogenic burning in the local region. Conclusions: New Zealand forest plant communities appear to have experienced only relatively minor changes during the herbivore gap. Our results contradict long‐standing hypotheses that shrubs and ferns had flourished in New Zealand forest understoreys at this time, preventing podocarp regeneration. However, due to the relatively recent extinction of moa, and long life span of many forest trees, there may be an extinction debt where the long‐term consequences of moa extinction are still to be fully realized. Abstract : Large herbivores were absent from New Zealand between the mid‐15th Century AD (moa extinction) and the 19th Century AD (mammal introductions). We use soil pollen profiles to show that forest plant communities appear to have experienced only relatively minor changes during the 'herbivore gap', contradicting long‐standing hypotheses that forest understoreys flourished with shrubs and ferns, preventing podocarp regeneration.